2010
DOI: 10.1149/1.3264625
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Metal Induced Lateral Crystallization of Ge Using Germanide Forming Metals

Abstract: Low temperature ͑ranging from 350 to 420°C͒ metal induced lateral crystallization of Ge using germanide forming metals Ni, Co, and Pd is performed. The lateral growth lengths and crystallized Ge films' quality are optimized when annealed at 375°C, above which self-nucleation in Ge hinders the metal induced crystallization process. At 375°C, the sample with Pd as the seed metal has the largest lateral growth length, while the sample using Co as the seed layer exhibits the largest crystal grain size. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…58 The theoretical and experimental studies on the lattice alignment of NiGe and Ge revealed that NiGe{100}//Ge{110} was the best match. 47,59,60 Figure 5 shows the NiGe{100}//Ge{110} lattice matching relationship predicted from the lattice parameters. From a Ge lattice constant of 0.566 nm, the lattice mismatch in NiGe{100}//Ge{110} was estimated to be 1.2% in the baxis direction and 2.9% in the c-axis direction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 The theoretical and experimental studies on the lattice alignment of NiGe and Ge revealed that NiGe{100}//Ge{110} was the best match. 47,59,60 Figure 5 shows the NiGe{100}//Ge{110} lattice matching relationship predicted from the lattice parameters. From a Ge lattice constant of 0.566 nm, the lattice mismatch in NiGe{100}//Ge{110} was estimated to be 1.2% in the baxis direction and 2.9% in the c-axis direction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…38−40 Using MILC for Si, stable TFT performance was demonstrated. 41−43 The MILC of Ge has also been investigated using various metal catalysts, such as Ni, 44−48 Co, 47,48 Pd, 47,48 Cu, 48,49 Sn, 50 and Au. 51 MILC of Ge at low temperatures (<400 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] In line with this, metal-induced crystallization (MIC) of amorphous Ge (a-Ge) films on insulators has been studied for over a decade. [9][10][11][12][13] In the MIC, catalytic metals (Ni, Au, Cu, etc.) enable the low-temperature crystallization of a-Ge in the temperature range 150-400 • C, [9][10][11][12][13] which are significantly lower than the crystallization temperatures of a-Ge without the metals.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] In the MIC, catalytic metals (Ni, Au, Cu, etc.) enable the low-temperature crystallization of a-Ge in the temperature range 150-400 • C, [9][10][11][12][13] which are significantly lower than the crystallization temperatures of a-Ge without the metals. 2,14,15 In particular, a nanowire-like single-crystal Ge is achieved by metal-induced lateral crystallization (MILC), which is promising for high-speed Ge transistors.…”
mentioning
confidence: 99%